Analiza wypowiedzi pracowników domów opieki społecznej na temat ich własnego sposobu rozumienia i doświadczania dorosłości przez podopiecznych - Myśliwczyk, Iwona (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Experiencing institutions by adults with mental retardation still evokes controversy in literature. The study presents the results of the research on the analysis of narratives by long-term care centre workers. The reality they experienced revealed ‘subjective truth’ about adult lives of mentally retarded people. The analysis of the narratives showed both the personnel’s work which can support, initiate and create adult lives in institution and work which can impair people’s functioning to such an extent that they become passive, withdrawn and isolated. More often mentally retarded adults in institutions experience limitations which affect their lives and create them according to a particular pattern. The lives of adults with mental retardation depend on personnel’s approach and attitude towards a group.